(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study included four aspects: Collection of 200 samples of patients with four different pathogenic cases: Burns infections, Wound infections, Urinary Tract Infections & diarrhea , for period ( September 2016 – March2017) . 403 bacterial isolates were got. Gram negative bacteria represented 329 isolates (48.9% E.coli ). The percentages of E.coli isolates are different depending on isolation sources and the Urinary Tract Infections have the highest (72.2%). Antibiotic Susceptibility test was performed for 10 antibiotics, all isolates of E.coli showed perfect resistance against Penicillins & Cephalosporins while they have high sensitivity to Nitrofurantion . The other 6 antibiotics have different effects depending on the isolation sources. Natural Honey has potential high ability for E.coli growth inhibiting without any influence with isolation sources , MIC of Ntural Honey is 15%. The inhibition activity was tested for Ethanol (95%) Extracts of four Medicinal plants : Allium sativum , Paganum harmala , Nigella sativum & Myrtus communs . All of these extracts have high inhibitory effect on E.coli isolates without any influence of the isolation sources. Allium sativum extract has the highest effect with inhibition zone diameters (20.1-32.0) mm.